Comparison of Netilmicin with Gentamicin in the Therapy of Experimental Escherichia coli Meningitis - Scheld, W. Michael (1978)
Netilmicin (SCH 20569), a new broad-spectrum aminoglycoside derived from sisomicin, was compared with gentamicin in the therapy of experimental Escherichia coli meningitis in rabbits. Meningitis was produced in 48 animals by the intracisternal inoculation of 10(5)E. coli colony-forming units. The minimum bactericidal concentration was 2 μg/ml against the test strain for both gentamicin and netilmicin. The two aminoglycosides demonstrated comparable penetration into the cerebrospinal fluid (CSF). The mean percent penetration [(CSF concentration/serum concentration) × 100%] was 22.5 ± 6.0 and 20.6 ± 7.2 for netilmicin and gentamicin, respectively (P = 0.18). However, netilmicin achieved bactericidal activity in the CSF at lower levels than did gentamicin. When mean CSF concentrations ranged from 4 to 8 μg/ml, mean CSF bacterial titers decreased 2.98 logs in rabbits treated with netilmicin but only 0.16 log in rabbits treated with gentamicin. A 2-log decrease in CSF bacterial counts was produced by a mean CSF concentration of 1.4 μg of netilmicin per ml as compared to 14.1 μg of gentamicin per ml. Because of its reduced toxicity and greater in vivo bactericidal activity, netilmicin may offer an advantage over gentamicin in the therapy of gram-negative bacillary meningitis.